Targeted Myoglobin Delivery as a Strategy for Enhancing the Sensitivity of Hypoxic Cancer Cells to Radiation - Zaofeng Yang; Bradley S. Heater; Clayton T. Cuddington; Andre F. Palmer; Marianne M.M. Lee; Michael K. Chan (iScience, 2020)
Summary: The effectiveness of cancer radiotherapy is frequently hindered by the hypoxia of the tumor microenvironment. Direct delivery of oxygen to hypoxic tumor tissues is an attractive strategy to overcome this hypoxia-associated radioresistance. Herein, we report the generation of submicron-sized particles comprising myoglobin fused to the crystal-forming domain of Cry3Aa protein for the targeted delivery of oxygen to cancer cells. We demonstrate that myoglobin-containing particles were successfully produced in Bacillus thuringiensis with the assistance of the Cry3Aa domain I. Furthermore, these particles could be genetically modified to incorporate the cell penetrating peptide TAT and cell targeting peptide A549.1, resulting in particles that exhibited improved cellular uptake and targeting toward A549 cells. Notably, these myoglobin-containing particles increased the intracellular oxygen levels of A549 cells and thereby sensitized them to radiation. These findings suggest that the targeted delivery of O2-bound myoglobin could be an effective approach to enhance the efficacy of radiotherapy.